On factorizations of limited solubly ω-saturated formations - Selkin, V. (Algebra and Discrete Mathematics, 2012)
If F = F₁…Ft is the product of the formations F₁,…,Ft and F ≠ F₁…Fi−₁Fi+₁…Ft for all i = 1,…,t, then we call this product a non-cancellative factorization of the formation F. In this paper we gives a description of factorizable limited solubly ω-saturated formations.